2011
DOI: 10.1111/j.1564-913x.2011.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Public pensions' sustainability and population ageing: Is immigration the solution?

Abstract: Abstract. Population ageing generates problems of financial sustainability for unfunded pension systems in many developed countries. Immigration is often presented as one potential solution to this problem, mainly in countries with high migration inflows. The authors propose a model to analyse the impact of immigration flows on the financial sustainability of the pay‐as‐you‐go method, using Spain as a test case. They show that, despite their size, these inflows do not solve the Spanish pension system's sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
(18 reference statements)
1
18
0
3
Order By: Relevance
“…[17] has suggested that a pension system's sustainability will be enhanced if the fertility rate is increased; ref. [18] have claimed that financial sustainability of unfunded pension systems will be eroded by population ageing and analyzed the impact of immigration flows on the financial sustainability, taking Spain as a test case.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[17] has suggested that a pension system's sustainability will be enhanced if the fertility rate is increased; ref. [18] have claimed that financial sustainability of unfunded pension systems will be eroded by population ageing and analyzed the impact of immigration flows on the financial sustainability, taking Spain as a test case.…”
Section: Literature Reviewmentioning
confidence: 99%
“…het gemiddeld loon van de autochtone werknemers of het gemiddelde van alle werknemers en (v) de bijdragevoet op het loon voor de pensioenuitkering. Serrano et al (2011) combineren dit met een demografische projectie van het Spaanse instituut voor de statistiek voor de periode 2002-2059. In dit scenario groeit het aandeel van de werknemers van buitenlandse origine in de Spaanse actieve bevolking van 13% tot 26% in 2027 om nadien op dit peil constant te blijven.…”
Section: "unclassified
“…Reference [19] discusses the same aspects in the Basque Country. Reference [20] focuses on the impact immigration has on the viability and sustainability of the public pension system. The impact of immigration on the labor market is also the focus of numerous studies: [21] or the successive reports prepared for the Permanent Observatory of Immigration under the Ministry of Labor and Immigration ( [22] [23]).…”
Section: The Phenomenon Of Immigration: Previous Studiesmentioning
confidence: 99%